Penerapan Konseling Individu Dengan Teknik Thought Stopping Dalam Mengatasi Kecanduan K-Pop - Relita, Liah; Razzaq, Abdur; Jannati, Zhila (CV. ITTC INDONESIA, 2023)
Kpop addiction is against Islamic teachings. Kpop addiction can cause a person to be too excessive or obsessed with the idol they like. To find out the description of K-Pop addiction in client